استدراكات الإمام حسين الرجراجي الشوشاوي على النَّاظم علي بن محمد بن بري-رحمهما الله تعالى-من خلال كتابه الأنوار السواطع على الدرر اللوامع - شـبرو, ليلى; قـدة, كمال (جامعة الوادي university of eloued, 2022)
ملخص: يُعتبر الإمام الشوشاوي من صفوة العلماء الذين أفنوا أعمارهم في خدمة هذا الدين، تدريسا وإقراءً وتأليفا، فهو الأستاذ المقرئ النظّار بلا منازع، ودليل ذلك مؤلفاته النَّفيسة التي خلَّفها كمخطوطة الأنوار السواطع على الدرر اللوامع الذي تُعد من أهم ما أُلّفت في قراءة الإمام نافع، لأن صاحبها أودع فيها جملة من الفنون والمعارف التي منها الاستدراكات على النَّاظم، لذا جاء هذا البحث الموسوم بـ: "استدراكات الإمام حسين الرجراجي الشوشاوي على النَّاظم علي بن محمد بن بري-رحمهما الله تعالى- من خلال كتابه الأنوار السواطع على الدرر اللوامع"، ليُعرِّف بالإمامين الشوشاوي وابن بري-رحمهما الله تعالى- وبكتابيهما، ثم يذكر استدراكات الإمام على النَّاظم ابن بري ، ليصل في الختام لجملة من النتائج والتوصيات، ومن تلك النتائج: 1.أن للإمام الشوشاوي قدما راسخة في هذا العلم، ظهر ذلك من خلال استدراكاته على النَّاظم ابن بري. أنَّ استدراكات الإمام الشوشاوي على النَّاظم ليست من باب نقده، بل هي من باب التنبيه على النقص، أو تصحيح مفهوم، أو دفع التوهم. Abstract : Imam Shoshowi is considered one of the elite scholars who have spent his life in the service of this religion, teaching, reading and writing, he is the undisputed reader of the glasses, and the proof of this is his precious works left behind, such as the manuscript of the lights shining on the shiny pearls, which is one of the most important things that was written in the reading of Imam Nafi, because the owner deposited a number of arts and knowledge, including the catch-ups on the regulator, so this research was marked by: "Imam Hussein al-Rajraji al-Shoshawi's responses to the organizer Ali bin Mohammed bin Barre- May Allah rest them in peace- through his book The Lights on the Shiny Al-Darr", to be known as imams Al-Shoshowi and Ibn Berri, may Allah rest their soul. Their writings, and then mention the recitations of Imam Ali al-Nazim Ibn Berri, to reach in conclusion a number of results and recommendations, including: Imam Shoshowi has a well-established foot in this science, which was shown by his recitations on the organizer Ibn Berri. Imam Shoshoy's responses to al-Nazim are not a matter of criticism, but rather a warning of inferiority, correcting a concept, or pushing suspicion
Reflections Of Imam Husayn Al-rajaji Al-shushawi On The Regulator Ali Bin Muhammad Bin Berri - May God Almighty Have Mercy On Them - Through His Book “the Shining Lights On The Shining Pearls
مقال
Keywords: الإمام الرجراجي الشوشاوي ; النَّاظم ابن بري ; الأنوار السواطع على الدرر اللوامع ; الاستدراكات; Imam Al-Rajraji Al-Shoshouwi ; Al-Nazim Ibn Berri ; Al-Anwar al-Sawa.